Environment, Nuclear Energy and Public Perception - Hans Blix (Widyanuklida, 1998)
The famous Indian nuclear scientist, Dr. Homi Bhabha, coined the expression "no energy is more expensive than no energy". He meant that nothing is grimmer than living without any other energy than that of your own body. For a good life we need energy for cooking, heating, transportation, industrial production, communication, home appliances ... We take our cars. elevators. dish-washers, central heating and computers for granted in the industrialized societies. When we need power, we just plug in. Our energy and especially electricity consumption is big. The US uses some 13,500 kWh per person and year; my own country, Sweden, some 15000. But at the other end of the spectrum we have countries like Chad and Tanzania with less than 100 kWh per person and year. Nothing is more certain - and reasonable - than that countries at the lower end will seek to improve the lives of their people by increasing their energy and electricity consumption. * After-dinner speech delivered on Global Foundation, Inc. Conference on "Environment and Nuclear Enery", Washington DC, 28 Oktober 1997. Artikel ini diambil dari situs www.iaea.or.at